Blood flow restriction‐enhanced platelet‐rich plasma: A pilot randomised controlled trial protocol - Muhammad Ayyan (16328986) (2025)
Purpose To assess platelet‐rich plasma (PRP) changes in platelet and leucocyte count, insulin‐like growth factor 1 (IGF‐1), and interleukin 6 (IL‐6) concentration after bilateral low‐load knee extensions under blood flow restriction (BFR). Methods The present randomised controlled trial protocol will include two groups: the intervention group, which will undergo bilateral knee extensions under BFR, and the control group, which will perform bilateral knee extensions without BFR. Participants will be randomly allocated in a 1:1 ratio. Twenty‐two healthy individuals will be enrolled if the predefined inclusion criteria are met: (1) males, (2) ages 18–40, (3) Tegner activity level ≥5 and (4) with no musculoskeletal conditions that would interfere with exercise. Exclusion criteria include (1) individuals with systemic inflammatory diseases, (2) cardiovascular risk factors, (3) any blood dyscrasia, (4) Tegner Activity scale scores <5, (5) under nonsteroidal anti‐inflammatory drugs and aspirin treatment within one week before testing or (6) that had previously performed exercises on the testing day. The participant will perform low‐load bilateral knee extensions under BFR following a standard protocol of 30‐15‐15‐15 repetitions of consecutive sets with 30‐s rest intervals at 80% of limb occlusive pressure and 30% of 1‐RM load. PRP platelet and leucocyte count, IGF‐1 and IL‐6 concentration measurements (via flow cytometry, chemiluminescence testing and immunochromatography, respectively) will be conducted before exercise and 10, 20 and 30 min after the intervention. Results The expected outcome is that the standard protocol of low‐load bilateral knee extensions under BFR will increase the platelet and leucocyte count, IGF‐1 and IL‐6 in the PRP preparation. Conclusion The current protocol allows the study of an enhanced PRP formulation for its potential implementation in multiple sports injuries. Other Information Published in: Journal of Experimental Orthopaedics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jeo2.70034